Kalibrasi Model Epanet Dengan Uji Paired Sample Test pada Tinggi Tekan Model dan Tinggi Tekan Aktual - Benson Limbong; Suripin; Sudarno (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Local state drinking water company, Tirta Moedal, which its service area includes Mijen district, need to anticipate growing number of customers along with rapid growing population in the area for the last 5 years. One of the technical preparation is creation of Epanet model of pipe distribution network. Epanet model usage in water pipe network is addressed for time efficiency in hydraulics calculation if there are pipe network development. Calibration in water pipe model is comparing model simulation result to actual observation value of water pressure, by Paired Sample Test. Rising pipe life causing rising roughness and increasing headloss. The goal of this research is to calibrate the Epanet simulation model to actual condition by using modified roughness C value, conform to pipe age. Calibration results show average model simulation pressure is 20.92 m and average actual pressure is 18.94 m. Paired sample T test 2 tailed were conducted to both average pressure , resulting there is no real difference between simulation model to observation actual value, indicated by significant value is 0,124 > 0,05, the model is valid.